2022
DOI: 10.1111/maec.12728
|View full text |Cite
|
Sign up to set email alerts
|

Feeding guilds among batoids in the northwest coast of the Baja California Sur, Mexico

Abstract: Research on the feeding habits of batoids provides information of intra and interspecific interactions of this taxon in marine ecosystems. We analyzed 832 stomachs of nine ray species collected from the artisanal fishery on the Northwest coast of Baja California Sur (NBCS). We identified 79 prey items assembled in five trophic groups (crustaceans, fish, mollusks, polychaetes, and sipunculidae). Results indicated that the red crab Pleuroncodes planipes was the most important prey in the diet of the seven batoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…For example, dental cusps are absent in the dentition of extant guitarfishes (Batomorphii, Elasmobranchii), such as Rhina ancylostoma and Zapteryx exasperate (see Herman et al, 1997 ; Berkovitz and Shellis, 2017 ). Nevertheless, their un-cuspidate dental plates do not prevent these batoids from occasionally consuming small teleost fishes in addition to their main prey (e.g., crustaceans; Purushottama et al, 2022 ; Reyes-Ramíre et al, 2022 ). In elasmobranchs, variation of the “niche breadth” ( sensu Bazzi et al, 2021 ) is crucial for avoiding resource competition between predators with similar trophic adaptations, such as dental plates in batoids (see Bornatowski et al, 2014 ; Munroe et al, 2014 ; Lear et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dental cusps are absent in the dentition of extant guitarfishes (Batomorphii, Elasmobranchii), such as Rhina ancylostoma and Zapteryx exasperate (see Herman et al, 1997 ; Berkovitz and Shellis, 2017 ). Nevertheless, their un-cuspidate dental plates do not prevent these batoids from occasionally consuming small teleost fishes in addition to their main prey (e.g., crustaceans; Purushottama et al, 2022 ; Reyes-Ramíre et al, 2022 ). In elasmobranchs, variation of the “niche breadth” ( sensu Bazzi et al, 2021 ) is crucial for avoiding resource competition between predators with similar trophic adaptations, such as dental plates in batoids (see Bornatowski et al, 2014 ; Munroe et al, 2014 ; Lear et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the construction of the diet matrix, the information was obtained from the literature (e.g., Sampson et al, 2010;Flores-Ortega et al, 2014;Hermosillo-Núñez et al, 2018;Calderon-Aguilera et al, 2021;Reyes-Ramírez et al, 2022) from studies carried out in sites close to the location of this study. It is important to mention that a recent study has showed that interaction matrices based on stomach content analysis is enough robust for assessing the trophic complexity and macroscopic properties (Ortiz, 2018).…”
Section: Introductionmentioning
confidence: 99%